Sistem Prediksi Jumlah Wisatawan Di Lambangan Pauno Desa Kendek Menggunakan Metode Support Vector Machine - Hermawan, Tamsil; Yasin Aril Mustofa; Kartika Chandra Pelangi (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2024)
Abstrac- Banggai Laut is regency rich in agricultural products and marine beauty. One of the very famous tourist attractions in Banggai Laut is Lambangan Pauno Beach. Lambangan Pauno Beach is one of the beachside tourist attractions at Kendek in Banggai Utara Subdistrict, which is 10 km from Banggai City. Lambangan Pauno is a very representative tourist attraction because it can be reached by car or motorbike. It extends for about 200 meters with clean white sand, coral rocks, cliffs, and Ketapang trees, fencing on the left and right ends of the beach, making the view beautiful. Lambangan Pauno has become a tourist spot in Banggai Laut often visited by tourists. Tourist visits have increased drastically due to many factors, including competitive travel costs and the number of adequate travel routes. It is supported by facilities that make visitors comfortable and guarantee security. Based on the research results, it is found that the research categorization produced by SVM is very good. It is proven by the test results which produce an accuracy rate of 90%. Keywords: prediction system, number of tourists, SVM